A campaign aimed at increasing seasonal influenza vaccination coverage among post graduate medical residents in an Italian teaching hospital. Issue 4 (3rd April 2019) - Barbara, Andrea; Mariani, Marco; De Waure, Chiara; Anzelmo, Vincenza; Piccoli, Bruno; Cambieri, Andrea; Damiani, Gianfranco; Ricciardi, Walter; Laurenti, Patrizia
ABSTRACT: We analysed the impact of several strategies aimed at increasing influenza immunisation rates among Medical Residents (MRs) of an Italian teaching Hospital. During the 2015–16 and 2016–17 influenza seasons we carried out several interventions: ambulatory doubling where vaccination was offered, ambulatory opening hour extension, email invitations, informative materials, forum theatre and vaccination campaign conference. In addition, during the 2016–17 the OSV was carried out: MRs who go to specific wards where they perform influenza immunisation counselling and eventually vaccinate the personnel. 99/1041 (9.5%) and 184/1013 (18.2%) MRs received the vaccine in 2015–16 and in 2016–17 respectively (p < 0.0001). Significant difference was found among three specialisation areas (medicine, surgery, "services"; p < 0.001) and among years of residency (p < 0.001). The highest coverage was found among Infectious Diseases, Paediatrics, Haematology and Hygiene MRs (80%, 67%, 52% and 52% respectively) in 2016–2017 season. The highest coverage increase was found among MRs in Pneumology and Geriatrics (566% and 268%, respectively). The coverage rate has increased even though important differences among specialties persist. The study shows a significant increase in immunisation rate among MRs after the implementation of these strategies.